Spatial Correlates of U.S. Heights and BMIs, 2002 - John Komlos; Benjamin E. Lauderdale (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
Aiming to further explore possible underlying causes for the recent stagnation in American heights, this paper describes the result of analysis of the commercial U.S. Sizing Survey. Using zip codes available in the data set, we consider geographic correlates of height such as local poverty rate, median income, and population density. We find that after adjusting for variables known to influence height such as income and education, population density is negatively correlated with height among white men, but only marginally among white women. Similar analysis of Body Mass Index (BMI) also shows a negative correlation with population density after adjustment for income, education, and age for both sexes. Local economic conditions as measured by median income, unemployment rate or poverty rate do not have a strong correlation with height or weight after adjusting for individual income and education.
urn:nbn:de:bvb:19-epub-466-9
Keywords: D60; I10; I31; J15; 330; Height; Biological Standard of Living; Anthropometry; Social inequality; Health; Physical Stature; BMI; Weight